PENERAPAN TEKNOLOGI PENYIRAM TANAMAN BERBASIS IoT DENGAN SENSOR pH DAN PPM DILENGKAPI DENGAN GOOGLE ASSISTANT UNTUK PETANI DESA BEBENGAN KABUPATEN KENDAL: PENERAPAN TEKNOLOGI PENYIRAM TANAMAN BERBASIS IoT DENGAN SENSOR pH DAN PPM DILENGKAPI DENGAN GOOGLE ASSISTANT UNTUK PETANI DESA BEBENGAN KABUPATEN KENDAL - Ilham Sayekti; Dadi; Devi Yesitasari; Faizah; M. Cahyo Ardi Prabowo; Septiantar Tebe Nursaputro; Sheilla Nadia Valina; Sihono; Sri Astuti; Supriyati; Tulus Pramuji; Wahyu Sulistiyo (Politeknik Negeri Semarang, 2026)
Vegetable farmers in Bebengan Village, Kendal Regency, still mostly water their crops manually, resulting in inefficient water usage and inconsistent watering timing. Additionally, the water quality for irrigation has not been monitored regularly, even though pH and PPM parameters affect nutrient availability and plant growth. This service activity aims to implement an Internet of Things (IoT)-based automatic plant watering technology that can monitor pH and PPM and provide easy control through Google Assistant. The implementation methods include observing partner needs, designing and assembling an Arduino ATmega 2560 and ESP8266-based system with pH and PPM sensors, installing it on a 200 m² cultivation area, integrating remote monitoring and control, and training farmers on operating and maintaining the equipment. Implementing the system allows for more scheduled/controlled watering and provides real-time pH and PPM information as a basis for decision-making. In conclusion, the implementation of this IoT system improves the effectiveness of the watering process, supports water quality monitoring, and simplifies operations through voice-based control, thus potentially increasing cultivation efficiency at the farmer level.